Acute Effect of Resistance Exercise on Hemoglobin Level (HBG) Among Physically Trained Boys - Kishore Mukhopadhyay; Ghosh, Arnab (Journal of Sports Medicine and Therapy, 2025)
Introduction: In this research, the examination of the acute effect of resistance exercise on hemoglobin level of physically trained boys has been aimed. Methods: Ten (10) physical education male students with an average age of 23.16 ± 1.85 years participated in this study on voluntary basis. Hemoglobin level (HBG) of the students were analyzed Before Exercise (BE) and just after 35 minutes of resistance exercise (AE). In order to determine Hemoglobin level, blood samples with 5 ml EDTA were taken from the forearm ante-cubical area before and after resistance exercise, and analyzed in laboratory with using auto-analyzer (Sysmex XP- 100). Result: Measurement results were presented as average and standard deviation. Student’s t-test for dependent samples was used in order to make a comparison between BE and AE values. p < -0.01 value was considered to be significant. The result of the study revealed that, the increase in AE than BE values for Hemoglobin level significantly. Conclusion: Conclusively Hemoglobin level displayed significant increase in relation to acute resistance exercises.